Examining employment discrimination in South Africa, 1997–2016. Issue 4 (4th July 2018) - Fredericks, Fadwah; Yu, Derek
ABSTRACT: This study examines employment discrimination by race and gender in 1997–2016 by employing a sample that represents the labour force (excluding informal sector workers, agricultural workers, domestic workers, self-employed and employers) aged between 15 and 65 years. Probit models are conducted to estimate labour force participation, employment and occupational attainment likelihoods. This is followed by the Oaxaca–Blinder decomposition, and the results indicate that the unexplained component of the white–African employment probability gap reveals a downward trend in absolute terms in 2002–2014, but in relative terms it still accounts for about 50% of the gap in 2016. The unexplained component is most dominant in the male–female employment gap decomposition. While these results suggest that employment discrimination (unexplained component) against Africans and females remains serious, the improvement of education and skills level of the workseekers (explained component) from the previously disadvantaged groups remain crucial to improve their employment prospects.